Landmark and route knowledge in children’s spatial representation of a virtual environment - Nys, Marion; Gyselinck, Valérie; Orriols, Eric; Hickmann, Maya (Frontiers in Psychology, 2015)
This study investigates the development of landmark and route knowledge in complex wayfinding situations. Our study focuses on how children (aged 6, 8 and 10 years) and young adults (n=79) indicate, recognize, and bind landmarks and directions in both verbal and visuo-spatial tasks after learning a virtual route. Performance in these tasks is also related to general verbal and visuo-spatial abilities as assessed by independent standardized tests (attention, working memory, perception of direction, production and comprehension of spatial terms, sentences and stories). The results first show that the quantity and quality of landmarks and directions produced and recognized by participants in both verbal and visuo-spatial tasks increased with age. In addition, an increase with age was observed in participants’ selection of decisional landmarks (i.e. landmarks associated with a change of direction), as well as in their capacity to bind landmarks and directions. Our results confirm the view that children first acquire landmark knowledge, then route knowledge, as shown by their late developing ability to bind knowledge of directions and landmarks. Overall, the quality of verbal and visuo-spatial information in participants’ spatial representations was found to vary mostly with their visuo-spatial abilities (attention and perception of directions) and not with their verbal abilities. Interestingly, however, when asked to recognize landmarks encountered during the route, participants show an increasing bias with age toward choosing a related landmark of the same category, regardless of its visual characteristics, i.e. they incorrectly choose the picture of another fountain. The discussion highlights the need for further studies to determine more precisely the role of verbal and visuo-spatial knowledge and the nature of how children learn to represent and memorize routes.